Pond Inlet, Nunavut -- photograph ... - Seale, Linda N. (University of Alberta Library, 2000)
Display marking the celebrations for the creation of Nunavut, April 1 1999, showing the Nunavut flag and an Inuktitut name, Mitimatilik ('the place where Mitiima is buried'). Taken August 2000 ...